Towards Smart Village : Rides Management Mobile Application As Tourism Digital Promotion And Marketing in Society 5.0 Era - Hartatik Hartatik; Nurul Firdaus; Abdul Aziz (Universitas Dharma Wacana, 2022)
In the context of developing tourism in various regions in Indonesia, many areas are developing the potential around them to be used as tourist attractions that can attract visitors or what are then referred to as